Designing working diagrams for electrohydrodynamic printing. (31st August 2021) - Nie, Qichun; Ma, Qianli; Yang, Weili; Pan, Xiaolong; Liu, Zhongyi; Fang, Haisheng; Yin, Zhouping
Graphical abstract: Highlights: Leaky-dielectric model is considered for simulating the electrohydrodynamic (EHD) printing. Five dimensionless numbers based on the governing equations are firstly proposed. Effects of ink properties and operating parameters on the EHD printing are analyzed. Property and operating diagrams to optimize the EHD printing are identified. Abstract: Cone-jet is an important working mode that is critical to the accuracy of electrohydrodynamic (EHD) printing. This work considers the leaky-dielectric model and firstly proposes five independent dimensionless numbers, viz., the Ohnesorge number Oh, the Weber number We, the electric capillary number Ca E, the relaxation parameter α and the relative electrical permittivity of ink ε r, to delineate the cone-jet mode. Theoretical and computational analyses on the regime of cone-jet mode depicted by property and operating diagrams are performed. Theoretical analysis suggests that a cone-jet occurs in wide ranges of these dimensionless numbers. Computational analysis based on the finite element method narrows down these ranges. Complete working diagrams for the EHD printing are described in Oh-α and We - Ca E spaces, respectively. The theoretical and computational analyses well agree with previous experiments, which provides a general rule to optimize the EHD printing.